Development of a non-animal testing method using genetically engineered biosensors for assessing skin sensitizers - Seçilmiş, Melike; Katı, Ahmet; Eroğlu, Emrah (My University, 2024)
[Abstract Not Available]
Keywords: Biochemistry; Molecular Biology; Endocrinology; Metabolism